Experiences and Perspectives of Traditional Bullying and Cyberbullying Among Adolescents in Mainland China-Implications for Policy - Li, Jiameng; Hesketh, Therese (Frontiers in Psychology, 2021)
The prevalence of traditional bullying and cyberbullying is high among Chinese adolescents. The aims of this study are to explore: 1) characteristics of children who are targets or perpetrators of traditional bullying or cyberbullying; 2) causes of bullying in middle school; 3) reactions and coping strategies of bullying victims; and 4) impacts of bullying on victims’ psychosocial well-being. Students were selected based on the findings of previous quantitative research at schools in Zhejiang, Henan and Chongqing. Snowball sampling led to identification of more informants. Semi-structured interviews were conducted with students involved in traditional bullying and cyberbullying as perpetrators, victims and bystanders. Forty-one students aged 12-16 years (21 boys and 20 girls) from 16 schools in three provinces participated. Data collection and analysis followed a grounded theory approach. Among these students traditional bullying was much more common than cyberbullying, but there was a large overlap between the two types. The results informed a conceptual framework which identified the main causes of bullying in these settings: these included lack of education about bullying, inadequate classroom and dormitory management, and teachers’ failure to recognize and punish bullying. Children with specific characteristics, (such as being unattractive or low-achieving) were more likely to be bullied. Most victims lacked support of parents and teachers even when requested, leading to poor psychosocial well-being, difficulties with socialization, and poor academic performance. Our findings suggest that schools need to address bullying culture, through multi-faceted locally-appropriate approaches, based on zero tolerance. It is crucial to ensure that students, teachers and parents recognize the importance of such interventions.